Assessment of Transmitted HIV-1 Drug Resistance Mutations Using Ultra- Deep Pyrosequencing in a Turkish Cohort - Sili, Uluhan; Aksu, Burak; Tekin, Aysun; Hasdemir, Ufuk; Soyletir, Guner; Korten, Volkan (Current HIV Research, 2018)
Background: Antiretroviral treatment (ART) reduces morbidity and mortality caused by human immunodeficiency virus (HIV) infection; however, the emergence of drug-resistant strains poses an important obstacle to treatment success. Using conventional sequencing methods to determine antiretroviral resistance, mutations present in ≥20% of quasispecies can be identified, but drug-resistant minority variants can lead to virologic failure. Objective: We aimed to assess transmitted drug resistance mutations (TDRMs) within minority variants using ultra-deep pyrosequencing (UDPS). Method: Treatment-naive adult patients were included in this observational study. Surveillance TDRMs were classified as ≥20% or at minority variant level (≥2% – <20%). Genotypic sensitivity score calculated by using all pre-treatment drug resistance mutations (PDRMs) was also evaluated. Results: Thirty-six patients were analyzed. Any TDRM at ≥20% level was detected in 8.3% of the patients (n=3). This prevalence increased to 30.6% (n=11) with the inclusion of minority variants. All non-nucleoside reverse transcriptase inhibitor and protease inhibitor-related TDRMs were within minority variants. The genotypic sensitivity score of rilpivirine-based regimens was considerably diminished when minority variants were included in the PDRM analysis. Conclusion: UDPS was used for the first time to assess TDRM in a Turkish HIV cohort and uncovered several mutations hidden within minority variants. UDPS may be preferred to detect PDRMs for avoiding virologic failure with rilpivirine-based ART regimens.
Keywords: transmitted drug resistance